Population structure of the malaria vector Anopheles darlingi in Rondônia, Brazilian Amazon, based on mitochondrial DNA - Angêlla, Aline F [UNESP]; Gil, Luis HS; Silva, Luis HP da; Ribolla, Paulo EM (Instituto Oswaldo Cruz, Ministério da Saúde, 2007)
Anopheles darlingi is the most important Brazilian malaria vector, with a widespread distribution in the Amazon forest. Effective strategies for vector control could be better developed through knowledge of its genetic structure and gene flow among populations, to assess the vector diversity and competence in transmitting Plasmodium. The aim of this study was to assess the genetic diversity of An. darlingi collected at four locations in Porto Velho, by sequencing a fragment of the ND4 mitochondrial gene. From 218 individual mosquitoes, we obtained 20 different haplotypes with a diversity index of 0.756, equivalent to that found in other neotropical anophelines. The analysis did not demonstrate significant population structure. However, haplotype diversity within some populations seems to be over-represented, suggesting the presence of sub-populations, but the presence of highly represented haplotypes complicates this analysis. There was no clear correlation among genetic and geographical distance and there were differences in relation to seasonality, which is important for malarial epidemiology.
Keywords: malaria; Anopheles darlingi; mtDNA; ND4